Keberlanjutan Ketersediaan Beras di Kabupaten Pandeglang Provinsi Banten - Cahya, Maharanti Rian; Wibowo, Aris Supriyo; Bukhari, Ahmad (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
The gap between the demand and availibility of rice production in Pandeglang District must be maintained and even increased in number to maintain the availability of rice in Pandeglang District. This research aims to analyze the sustainability of rice availability at Pandeglang District based on sustainability index and status using a RAP-RICE ordination technique with Multi Dimensional Scaling (MDS) method. This study used primary and secondary data. Results of the MDS analysis RAP-RICE ordinary technique showed that a sustainability index of rice availability at Pandeglang District was 51.88 which categorized as sustainable sufficient. Analysis for five dimensions (ecology, economy, socio-culture, institution and technology) showed that a sustainability index of rice availability at Pandeglang District for economic dimension was relatively high, 57.10, respectively, which categorized as sustainable sufficient; the index for institution, ecological and technology dimensions were 42.58, 40.88, and 27.86 respectively, categorized as less sustainable; and the index for sosio-culture dimension was 22.54 which categorized as not sustainable. Results of leverage analysis indicated that 10 out of 30 attributes were sensitivity influential to sustainability of rice availability.